Detection Rates of PSMA-PET Radiopharmaceuticals in Recurrent Prostate Cancer: A Systematic Review - Soroush Rais-Bahrami; Phillip Davis; Albert Chau; Samuel J. Galgano; Brian F. Chapin; David M. Schuster; Catriona M. Turnbull (Diagnostics)
Background/Objectives: To conduct a systematic review to evaluate the detection rates (DR) of the three FDA-approved PSMA-targeted radiopharmaceuticals in patients with recurrent prostate cancer. Methods: Two individuals systematically searched MEDLINE, ScienceDirect, and Cochrane Libraries (February 2025), and independently reviewed all results to identify studies reporting patient-level 68Ga-PSMA-11, 18F-DCFPyL, or 18F-flotufolastat DR in ≥100 evaluable patients with recurrent prostate cancer. Sample-weighted means (SWM) of extracted DR were calculated. Results: Of 5059 published articles, 37 met our inclusion criteria, reporting data from 8843 patients undergoing 68Ga-PSMA-11 (n = 27), 18F-DCFPyL (n = 8), or 18F-flotufolastat (n = 2) studies. Heterogeneity was noted across enrolled populations, particularly in prior treatments. 68Ga-PSMA-11 studies recruited patients with marginally higher median PSA than 18F-DCFPyL or 18F-flotufolastat studies (median PSA ranged from 0.1 to 10.7, 0.2–2.5, and 0.6–1.1, respectively). Reported overall DR ranged from 25 to 91% for 68Ga-PSMA-11, 49–86% for 18F-DCFPyL, and 73–83% for 18F-flotufolastat, with SWM of 71%, 66%, and 79%, respectively. Post-prostatectomy DR were reported in 18 articles, resulting in SWM DR of 58% for 68Ga-PSMA-11 (n = 12), 55% for 18F-DCFPyL (n = 4), and 76% for 18F-flotufolastat (n = 2). Among post-radiotherapy patients, SWM were 87% for 68Ga-PSMA-11 (n = 4), 90% for 18F-DCFPyL (n = 2), and 99% for 18F-flotufolastat (n = 1). SWM DR at PSA < 1 ng/mL were 53%, 42%, and 66% for 68Ga-PSMA-11 (n = 13), 18F-DCFPyL (n = 5), and 18F-flotufolastat (n = 2), respectively. Conclusions: Considerable heterogeneity exists across populations in studies of diagnostic PET radiopharmaceuticals. Despite a paucity of 18F-DCFPyL and 18F-flotufolastat studies compared with 68Ga-PSMA-11, the available data suggest that all three radiopharmaceuticals provide high overall DR in patients with biochemical recurrence of prostate cancer.